Methodological pluralism or multimethod research in health and medical sciences - Srdjan Živanović; Jelena Pavlović; Natalija Hadživuković; Sandra Matović; Olivera Kalajdžić; Bojana Vuković; Ljubiša Kucurski (Биомедицинска истраживања, 2023)
Introduction: With the development of medical and health sciences, research problems have become more complex, and relying solely on quantitative or qualitative research approaches is no longer sufficient. The aim of this paper was to map the progress and trends in the scientific literature regarding the application of mixed studies in medical and health sciences. Methods: Bibliometric analysis was applied to meet the established goals. The Dimensions database was selected for literature search. The analysis unit consisted of 485 publications of various types, and the VosViewer program was employed for the analysis. Results: The results have shown that this topic in science has experienced an exponential decline in the last year. Additionally, the most productive authors, journals, and countries have been identified, along with their collaborative networks through visual co-citation analysis. Based on the analysis of word co-occurrence, we can conclude that words like "combined studies," "problem," "factors," "community" are most frequently repeated, indicating that the topics addressed in this domain mainly focus on investigating and addressing numerous issues in the field of medical and health sciences. Conclusion: Although the results indicate a decreased interest in this topic in the last year, it does not diminish the significance of this research. Progress in medical and health sciences requires a comprehensive approach to research, which includes both quantitative and qualitative methods, such as mixed studies. Understanding the current trends and available resources for researchers assists in achieving better outcomes and improving the quality of healthcare practice.
Keywords: mixed studies; medical sciences; health sciences; VosViewer